Nomination and remuneration committee: A review of literature - Ferdy Putra; Doddy Setiawan (Journal of Capital Markets Studies (JCMS), 2024)
Purpose This paper aims to synthesize the diverse literature on nomination and remuneration committees and provide avenues for future research. Design/methodology/approach This study provides a comprehensive literature review of theoretical and empirical studies published in reputable international journals indexed by Scopus. Findings The literature review reveals several aspects of the nomination and remuneration committee. These aspects have been classified into the definition of the nomination and remuneration committee, dimensions of the nomination and remuneration committee, measurement and research review results, reasons for conflict empirical findings, company dynamics and research on moderators, as well as recommending future research. Research limitations/implications Our literature review shows that nomination and remuneration committees play a role in improving board performance and company performance, reducing agency conflicts and improving corporate governance to provide implications for companies, regulators and investors and pave the way for future research. Originality/value This paper identifies issues related to nomination and remuneration committees, their theoretical and practical implications and avenues for future research.
Keywords: 330; Company board; Company dynamics; Compensation; Corporate governance; Nomination and remuneration committee